Analisis Rantai Nilai Sebagai Upaya Untuk Meningkatkan Keunggulan Kompetitif (Studi Kasus Pada UD. Ijen Batik Bondowoso) - Nia Amelia Damayanti; Diyah Probowulan; Ari Sita Nastiti (Politeknik Negeri Jember, 2021)
UD. Ijen Batik Bondowoso is a company engaged in the production of batik for the Bondowoso and surrounding areas, even outside Java and abroad. Competition for batik products in Indonesia makes companies have to increase UD's competitive advantage. Ijen Batik needs to do a strategy. This study aims to analyze the value chain of batik products made at UD. Ijen Batik Bondowoso. Value chain analysis is one way of looking at business as a series of activities that convert inputs into outputs that are of value to customers. This research uses qualitative method with case study method. The type of data used is primary data and secondary data with data collection techniques through observation, interviews and documentation. The results show that the value chain actors consist of suppliers, companies, wholesalers and retailers. In the added value analysis conducted at the time of batik production, it shows an added value of 213,000.00 or 81.3%/per unit. This is because the highest added value is obtained from sales and marketing activities. Keywords: Value Chain Analysis, Competitive Advantage